2016
DOI: 10.2174/0929867323666160411143314
|View full text |Cite
|
Sign up to set email alerts
|

Berberine: New Insights from Pharmacological Aspects to Clinical Evidences in the Management of Metabolic Disorders

Abstract: Berberine is a quaternary ammonium salt from the protoberberine group of isoquinoline alkaloids found in such plants as gender Berberis. Berberine is recognised to improve glucose and lipid metabolism disorders and preliminary clinical evidences suggest the ability of berberine to reduce endothelial inflammation improving vascular health, even in patients already affected by cardiovascular diseases, suggesting a possible interesting role of berberine and its metabolites in clinical practice. However, its physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 120 publications
0
43
0
1
Order By: Relevance
“…Berberine, the principal isoquinoline alkaloid constituent of many popular medicinal plants (e.g., the Berberis , Coptis , and Hydrastis , among others; Figure a), has historically been used in traditional Chinese medicine due to its various biological activities, including antidiarrheal, anticancer, antidiabetic, antihyperlipidemic, and cardioprotective effects (Menees, Saad, & Chey, ; Pirillo & Catapano, ; H. L. Tan et al, ; W. Tan, Li, Chen, & Wang, ). Notably, berberine has attracted considerable attention because of its anti‐inflammatory activity in vitro and in vivo (Caliceti, Franco, Spinozzi, Roda, & Cicero, ; Seo, Fischer, & Efferth, ; Xie & Du, ). However, considering the extensive pharmacological effects of berberine and the complex molecular mechanisms of ALI, the protective effect of berberine against LPS‐induced ALI requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine, the principal isoquinoline alkaloid constituent of many popular medicinal plants (e.g., the Berberis , Coptis , and Hydrastis , among others; Figure a), has historically been used in traditional Chinese medicine due to its various biological activities, including antidiarrheal, anticancer, antidiabetic, antihyperlipidemic, and cardioprotective effects (Menees, Saad, & Chey, ; Pirillo & Catapano, ; H. L. Tan et al, ; W. Tan, Li, Chen, & Wang, ). Notably, berberine has attracted considerable attention because of its anti‐inflammatory activity in vitro and in vivo (Caliceti, Franco, Spinozzi, Roda, & Cicero, ; Seo, Fischer, & Efferth, ; Xie & Du, ). However, considering the extensive pharmacological effects of berberine and the complex molecular mechanisms of ALI, the protective effect of berberine against LPS‐induced ALI requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have reported the effectiveness of BBR in treating conditions such as chronic congestive heart failure, hypercholesterolemia, type 2 diabetes, polycystic ovary syndrome, and irritable bowel syndrome. 7 However, oral BBR has been reported to cause extrapyramidal system reactions, arrhythmia, liver dysfunction, and even death in clinics in China, 8 as well as acute toxicity in animals. 9 To guide rational clinical drug therapy, it is necessary to elucidate the pharmacokinetic properties of BBR.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine. Berberine (BBR), a quaternary ammonium salt from the protoberberine group of isoquinoline alkaloids (5,6-dihydrodibenzoquinolizinium derivative) found in Berberis species plants (Berberidaceae), exhibits many different types of biological activities, including its effectiveness in lipid disorders and hyperglycemia [166]. The poor intestinal absorption and bioavailability of BBR are the main drawback when orally administered even though its metabolites maintain higher concentration in plasma, behaving like the pharmacologically active forms of BBR; its main metabolite berberrubine (M1) tautomerizes to a highly conjugated, electroneutral quinoid structure [167] reaching a high plasma concentration as a consequence of a more efficient intestinal absorption [167].…”
Section: Other Emerging Antiatherogenic Nutraceuticalsmentioning
confidence: 99%